CRISPR-Cas: a brief overview - Sonmez, Yusuf Ercin (KIDNEYS, 2021)
CRISPR-Cas is an adaptive immunity in prokaryotes against infections by viruses and plasmids. CRISPR array recognizes foreign sequences of the invaders and Cas destroys them. Using this system seems possible to find the unwanted sequences in the genome and to destroy or to change them with the suitable ones. This system might not only protect ourselves from the future infections but also correct congenital abnormalities which may predispose to carcinogenesis or some congenital diseases.